Recent methods, sources and approaches in the study of temporal landscape change at different scales - a review - Lundberg, Anders (Hungarian Geographical Bulletin, 2018)
Landscape change can be studied at different scales, from local to regional, e.g. from a biodiversity level to the level of land-use systems. Historical sources such as land taxation papers, cadastral maps, agricultural and population censuses are not very much used in physical geography studies but this article explores the potential of historical sources and gives examples of how they can be used. Studies of landscape change requires an approach to the temporal dimension and examples are given on how this can be solved. At the biodiversity level, much attention is presently paid to red-listed species. The article gives an account of criteria used to evaluate red-list status of species and critically reviews the way governmental nature management bodies presently deal with this. Several long-term studies have been carried out recently and huge variations in population size of species from year to year have been detected. As an alternative to red-list status based on population size based on static data from one or a few years, the concept of the natural variation interval of a species is introduced. The article demonstrates how this phenomenon can be identified based on a temporal approach.